Muscle Injury Induced At the Time of Acute and Chronic Rotator Cuff Repair. Issue 7 (29th July 2014) - Davis, Max; Stafford, Patrick L.; Jergenson, Matthew; Bedi, Asheesh; Mendias, Christopher
Objectives: Rotator cuff tears are a common source of shoulder pain and disability. Even after surgical repair of these tears, many patients continue to have reduced shoulder function and a progression of intramuscular fatty degeneration. Previous work in a sheep model demonstrated that a slow, progressive lengthening of chronically torn cuff muscles followed by surgical repair of the tendon reversed fatty degeneration and improved muscle function. As patients with chronic cuff tears often experience a shortening of the muscle fibers, it is possible that repairing the torn tendon to its original anatomical footprint induces a massive stretch-induced muscle injury that could contribute to poor outcomes after repair. Evans Blue Dye (EBD) is a water soluble, membrane impermeable dye, that is used to identify muscle fibers that have suffered an injury to their plasma membrane. We hypothesized that, compared with acutely torn and repaired rotator cuff muscles, the substantial stretch that is required to repair a chronically torn and shortened rotator cuff would result in significant muscle fiber damage. Methods: This study was approved by our IACUC. Male Sprague-Dawley retired breeder rats (n=30) were placed into 5 groups: control, sham surgery, acute tear no repair, acute tear and repair, chronic tear no repair and chronic tear and repair, with each modality performed bilaterally (Fig 1A). An intraperitoneal injection of 1% EBD was administered 24 hours before the harvest surgery. At harvest, the supraspinatus muscles of each rat were removed and the length and mass of each muscle was measured. To determine EBD+ fibers the supraspinatus muscles were snap frozen in OCT and the muscles were cryosectioned and incubated with WGA-Lectin-AF488 to mark the extracellular matrix (ECM), DAPI to identify nuclei and EBD was used to identify the fibers with a damaged sarcolemma (Fig 1B-C). A one-way ANOVA (p<0.05) and Tukey's post-hoc sorting was used to evaluate the differences between groups. Results: Compared with controls, rats that had a chronic supraspinatus tear but did not undergo repair had a 35% decrease in muscle mass compared to controls, while rats that had a chronic tear and also underwent repair had a 24% decrease in wet mass compared to controls (Fig 1D). Both groups of rats that underwent a chronic tear experienced an approximate 20% decrease in supraspinatus length when compared to the muscle length of other groups (Fig 1E). In the sham, acute and chronic tear and repair groups there were a greater number of EBD+ fibers in the mid-distal region of the muscle than in the mid-proximal region (Fig 1F). At the mid-distal end of the control and chronic tear no repair groups there were very few EBD+ fibers, in the sham 27% of the fibers were EBD+ and the remaining groups had almost 90% EBD+ fibers (Fig 1F). At the mid-proximal portion of the muscle the chronic tear and repair group had nearly 70% EBD+ fibers while none of the other groups showed a significant increase in EBD+ fibers over the control group (Fig 1G). Conclusion: A massive injury to muscle fibers is induced when the tendons of chronically torn rotator cuffs are repaired to their anatomical footprint. The repair of chronically torn cuff muscles results in extensive injury throughout the muscle that may contribute to poor long-term surgical outcomes even in the setting of a structurally intact repair. Therapeutic interventions that protect the muscle fiber plasma membrane may improve outcomes in patients with rotator cuff tears.